Stable anchoring of bacteria-based protein nanoparticles for surface enhanced cell guidance. Issue 23 (13th May 2020) - Martínez-Miguel, Marc; Kyvik, Adriana R.; M. Ernst, Lena; Martínez-Moreno, Albert; Cano-Garrido, Olivia; Garcia-Fruitós, Elena; Vazquez, Esther; Ventosa, Nora; Guasch, Judith; Veciana, Jaume; Villaverde, Antonio; Ratera, Imma
Abstract : The preparation of robust nano–micropatterns for prolonged cell culture studies using covalent anchoring between the surface and protein nanoparticles, which are produced in a human-safe bacterial platform. Abstract : In tissue engineering, biological, physical, and chemical inputs have to be combined to properly mimic cellular environments and successfully build artificial tissues which can be designed to fulfill different biomedical needs such as the shortage of organ donors or the development of in vitro disease models for drug testing. Inclusion body-like protein nanoparticles (pNPs) can simultaneously provide such physical and biochemical stimuli to cells when attached to surfaces. However, this attachment has only been made by physisorption. To provide a stable anchoring, a covalent binding of lactic acid bacteria (LAB) produced pNPs, which lack the innate pyrogenic impurities of Gram-negative bacteria like Escherichia coli, is presented. The reported micropatterns feature a robust nanoscale topography with an unprecedented mechanical stability. In addition, they are denser and more capable of influencing cell morphology and orientation. The increased stability and the absence of pyrogenic impurities represent a step forward towards the translation of this material to a clinical setting.